Optical frequency comb Fourier transform spectroscopy with sub-nominal resolution and precision beyond the Voigt profile. (January 2018) - Rutkowski, Lucile; Masłowski, Piotr; Johansson, Alexandra C.; Khodabakhsh, Amir; Foltynowicz, Aleksandra
Highlights: First observation of collisional line narrowing with frequency comb spectroscopy. Entire 3ν1 + ν3 CO2 band measured in 12 min with precision beyond the Voigt profile. High-resolution broadband spectra recorded with no influence of the instrumental lineshape. Comb-based Fourier transform spectrometry with sub-nominal resolution is explained. Abstract: Broadband precision spectroscopy is indispensable for providing high fidelity molecular parameters for spectroscopic databases. We have recently shown that mechanical Fourier transform spectrometers based on optical frequency combs can measure broadband high-resolution molecular spectra undistorted by the instrumental line shape (ILS) and with a highly precise frequency scale provided by the comb. The accurate measurement of the power of the comb modes interacting with the molecular sample was achieved by acquiring single-burst interferograms with nominal resolution matched to the comb mode spacing. Here we describe in detail the experimental and numerical steps needed to achieve sub-nominal resolution and retrieve ILS-free molecular spectra, i.e. with ILS-induced distortion below the noise level. We investigate the accuracy of the transition line centers retrieved by fitting to the absorption lines measured using this method. We verify the performance by measuring an ILS-free cavity-enhanced low-pressure spectrum of the 3ν1 + ν3 band of CO2 around 1575 nm with line widths narrower than the nominal resolution. We observe and quantify collisional narrowing of absorption line shape, for the first time with a comb-based spectroscopic technique. Thus retrieval of line shape parameters with accuracy not limited by the Voigt profile is now possible for entire absorption bands acquired simultaneously.